Unveiling the potential of novel yeast protein extracts in white wines clarification and stabilization - Fernandes, Joana P.; Neto, Rodrigo; Centeno, Filipe; De Fátima Teixeira, Maria; Gomes, Ana Catarina (Frontiers in Chemistry, 2015)
Fining agents derived from animal and mineral sources are widely used to clarify and stabilize white wines. Nevertheless, health and environmental problems are being raised, concerning the allergenic and environmental impact of some of those fining products. In this study, our aim is to validate the potential of non-allergenic protein extracts, obtained from an alternative and safe source, naturally present in wine: oenological yeasts. Three untreated white wines were used in this work in order to evaluate the impact of these novel yeast protein extracts (YPE) in terms of the wine clarification and stabilization improvement. Two separated fining trials were thus conducted at laboratory scale and the yeast alternatives were compared with reference fining agents, obtained from mineral, animal and vegetable origins. Our results indicate that yeast protein extracts were capable to promote (i) brilliance/color improvement, (ii) turbidity reduction (76-89% comparing with the untreated wines) and (iii) production of compact and homogeneous lees (44% smaller volume than obtained with bentonite). Additionally, after submitting wines to natural and forced oxidations, YPE treatments revealed (iv) different forms of colloidal stabilization, by presenting comparable or superior effects when particularly compared to casein. Altogether, this study reveals that yeast protein extracts represent a promising alternative for white wine fining, derived from an entirely non-allergenic and sustainable origin.